Transcriptional instability is not a universal attribute of aging - Warren, Luigi A.; Rossi, Derrick J.; Schiebinger, Geoffrey R.; Weissman, Irving L.; Kim, Stuart K.; Quake, Stephen R. (Aging cell, 2007)
Summary It has been proposed that cumulative somatic mutations contribute to the aging process by disrupting the transcriptional networks that regulate cell structure and function. Experimental support for this model emerged from a recent study of cardiomyocytes that showed a dramatic increase in the transcriptional heterogeneity of these long‐lived postmitotic cells with age. To determine if regulatory instability is a hallmark of aging in renewing tissues, we evaluated gene expression noise in four hematopoietic cell types: stem cells, granulocytes, naïve B cells and naïve T cells. We used flow cytometry to purify phenotypically equivalent cells from young and old mice, and applied multiplexed quantitative reverse transcription–polymerase chain reaction to measure the copy number of six different mRNA transcripts in 324 individual cells. There was a trend toward higher transcript levels in cells isolated from old animals, but no significant increase in transcriptional heterogeneity with age was found in the surveyed populations. Flow cytometric analysis of membrane protein expression also indicated that cell‐to‐cell variability was unaffected by age. We conclude that large‐scale regulatory destabilization is not a universal concomitant of aging, and may be of significance as an aging mechanism primarily in nonrenewing tissues.